Single-mode erbium fiber dual-ring laser with 60-nm workable wavelength tunability. (June 2019) - Yang, Y.L.; Yeh, C.H.; Tsai, C.K.; Xie, Y.R.; Luo, C.M.; Chang, Y.J.; Chen, J.H.; Chow, C.W.
Highlights: A widely tunable and stable SLM erbium-doped fiber ring laser is achieved. The unpumped EDF-SA and dual-ring structure are used for side-mode suppression simultaneously. The proposed dual-ring scheme can spread the bandwidth from 1520.0 to 1580.0 nm. Abstract: In this investigation, to reach a widely wavelength-selectable and stable single-longitudinal-mode (SLM) erbium-doped fiber (EDF) ring laser, the unpumped EDF-based saturable absorber (SA) and dual-ring structure are used simultaneously for thickly multi-longitudinal-mode (MLM) suppression. The dual-ring scheme can spread the operation range of gain medium from 1520.0 to 1580.0 nm only by using a C-band erbium-doped fiber amplifier (EDFA). Moreover, the dual-ring scheme and EDF-based SA also could suppress the MLM noise for SLM oscillation. In the tuning range, the Lorentzian 3 dB linewidth is also obtained between 15 and 22 kHz in the wavelength range.